Distribution of GABAergic cells in the inferior colliculus that project to the thalamus - Mellott, Jeffrey G.; Foster, Nichole L.; Nakamoto, Kyle T.; Motts, Susan D.; Schofield, Brett R. (Frontiers in Neuroanatomy, 2014)
A GABAergic component has been identified in the projection from the inferior colliculus (IC) to the medial geniculate body (MG) in cats and rats. We sought to determine if this GABAergic pathway exists in guinea pig, a species widely used in auditory research. The guinea pig IC contains GABAergic cells, but their relative abundance in the IC and their relative contributions to tectothalamic projections are unknown. We identified GABAergic cells with immunochemistry for glutamic acid decarboxylase (GAD) and determined that 21% of IC neurons are GABAergic. We then combined retrograde tracing with GAD immunohistochemistry to identify the GABAergic tectothalamic projection. Large injections of Fast Blue, red fluorescent beads or FluoroGold were deposited to include all subdivisions of the MG. The results demonstrate a GABAergic pathway from each IC subdivision to the ipsilateral MG. GABAergic cells constitute 22% of this ipsilateral pathway. In addition, each subdivision of the IC had a GABAergic projection to the contralateral MG. Measured by number of tectothalamic cells, the contralateral projection is about 10% of the size of the ipsilateral projection. GABAergic cells constitute about 20% of the contralateral projection. In summary, the results demonstrate a tectothalamic projection in guinea pigs that originates in part from GABAergic cells that project ipsilaterally or contralaterally to the MG. The results show similarities to both rats and cats, and carry implications for the role of GABAergic tectothalamic projections vis-à-vis the presence (in cats) or near absence (in rats and guinea pigs) of GABAergic interneurons in the MG.